Creating Sustainable Fiscal Space for Infrastructure : The Case of Tanzania - Ter-Minassian, Teresa (IMF Working Papers; Working Paper, 2008)
A common dilemma facing governments around the world is how to meet the sizeable fiscal costs of providing and maintaining infrastructure networks. Over the past decade, developed and developing countries have looked to fiscal rules, budgetary reforms, tax policy and administration measures, public-private partnerships and other innovative financial instruments to raise additional finance for infrastructure investment. This paper looks at the range of options for raising the financing to meet Tanzania's infrastructure needs. It begins with a brief survey of the evidence on the relationship between infrastructure, public investment, and economic growth, and then goes on to consider the case for additional infrastructure investment in Tanzania. The second part of the paper looks at five broad options for mobilizing additional resources to meet Tanzania's infrastructure needs: (i) direct private investment and PPPs, (ii) expenditure reprioritization and efficiency, (iii) domestic revenue mobilization, (iv) external grants and concessional financing, and (v) sovereign borrowing on domestic or international credit markets. The paper concludes with some general recommendations on what combination of the above approaches might be suitable for Tanzania.